KARAKTERISTIK, MOTIVASI DAN PERSEPSI WISATAWAN MANCANEGARA KE DESA WISATA TRUNYAN, KINTAMANI - Angga Pratama, I Putu; Dewi, LGLK.; Oka Karini, Ni Made (Jurnal IPTA (Industri Perjalanan Wisata); Vol 8 No 2 (2020): Jurnal IPTA (December 2020), 2020)
Tourists who travel to a tourism village certainly have different characteristics, motivations, and perceptions. These three things are very important to be identified, because they can become a reference material for the local community and the government related to self-improvements, facilities-improvements, infrastructure, management, and services in Trunyan Tourism Village that can affect the tourist and the returning of them, and are able to provide excellent service in accordance with the tourists expectations. The purpose of this study is to identify the characteristics, motivations, and perceptions of the foreign tourists who travel to Trunyan Tourism Village. Data collection techniques used in this research are observation, unstructured interviews, questionnaires, literature study, and documentation. Accidental sampling techniques used to take a sample of 100 people. Data analysis technique used in this study is descriptive qualitative data analysis technique. The results show that the most foreign tourists who travel to Trunyan Tourism Village are 33% from United States, 40% with an age range of 15-30 years old, 55% males, 29% working as employees, and 39% of master-educated. A total of 61% tourist state that the purpose of the travel is to travel/recreation, 65% state that the arrangement of the travel is arranged by the travel agency, 100% are first timers, 49% receive the information about Trunyan Tourism Village through the travel agency, 54% spend $39-$54, and 85% are accompanied by friends/family. The motivation that push foreign tourists to travel to Trunyan Tourism Village is novelty and knowledge seeking of 4.10, while the motivation that pull foreign tourists to travel to Trunyan Tourism Village is safety, cleanliness, and variety attraction of 3.71. The foreign tourists who travel to Trunyan Tourism Village have good perceptions/agree with the average total score of 3,60.